Host-Species Variation and Environment Influence Endophyte Symbiosis and Mycotoxin Levels in Chinese Oxytropis Species - Chenchen Guo; Li Zhang; Qianqian Zhao; Manfred Beckmann; Helen Phillips; Huizhen Meng; Chonghui Mo; Luis A. J. Mur; Wei He (Toxins, 2022)
Oxytropis plants are widely distributed in the grasslands in northern China. Some Oxytropis species have been reported to contain the mycotoxin swainsonine, an alkaloid which causes poisoning in livestock, referred to as locoism. Previous studies showed that endophytic fungi (Alternaria oxytropis) symbiotically associate with these Oxytropis species to produce swainsonine. However, the influence of variation within the Oxytropis genus on the fixation or loss of symbiosis and toxicity is poorly understood, as is the influence of environmental factors. Here we used a collection of 17 common Oxytropis species sampled in northern China to assess genetic diversity using genotyping by sequencing which was compared with the levels of the endophyte and swainsonine. Results showed that nine Oxytropis species have detectable A. oxytropis colonisation, and seven Oxytropis species contain sufficient swainsonine to be considered poisonous, whereas the rest may be non-toxic. Species variation rather than the genetic lineage was associated with the fixation or loss of endophyte and swainsonine production, which appears to have resulted from genetic drift. Genotype × Environment (G × E) effects were also found to influence endophyte and swainsonine levels amongst species of the Oxytropis genus. Our study will provide a better understanding about the evolutionary basis of A. oxytropis symbiosis and swainsonine biosynthesis in locoweeds.